A Review on Factors Influencing the Mismatch Losses in Solar Photovoltaic System - A. D. Dhass; N. Beemkumar; S. Harikrishnan; Hafiz Muhammad Ali (International Journal of Photoenergy)
In the last two decades, it is persistently emphasized to develop energy generation systems free from greenhouse gas emissions since these gases cause global warming, and it leads to unpredictable monsoons. Consequently, it might not be a conducive environment for human beings and animals to dwell. To ascertain the green environment for the next generations and reduce the use of fossil fuels, renewable energy sources are highly suggested to generate electrical energy. Solar photovoltaic is reckoned to be one of the promising methods to generate electricity; however, it has a lower conversion value due to various losses resulting from external and internal parameters. Among various losses that occurred in the solar photovoltaic system, mismatch loss is imperative, which causes the system to perform poorly. Solar photovoltaic systems have made topical advances in the use of highly effective solar cell materials to achieve high efficiency. In this analysis, performance parameters are influenced by the internal and external conditions of the solar photovoltaic systems and they lead to an increase in the loss of the system. The present review is focused to fetch fruitful information on the several studies that analyzed the effects on the solar photovoltaic systems of parasitic resistances, dust generated by tresses, clouds, solar radiation, temperature, relative humidity, different connection topologies, circuit implementation for partial shading, and remedies suggested by the potential authors.